Generalized compensation principle - Karl Schulz; Aleh Tsyvinski; Nicolas Werquin (Federal Reserve Bank of Chicago, 2022)
Economic disruptions generally create winners and losers. The compensation problem consists of designing a reform of the existing income tax system that offsets the welfare losses of the latter by redistributing the gains of the former. We derive a formula for the compensating tax reform and its impact on the government budget when only distortionary tax instruments are available and wages are determined endogenously in general equilibrium. We apply this result to the compensation of robotization in the U.S.
Keywords: 330; inequality; compensating variation; Kaldor-Hicks; distortionary taxes; general equilibrium; Equity; Justice; Inequality; and Other Normative Criteria and Measurement; Incidence; General Welfare; Well-Being